Electrochemical synthesis of AuPt nanoflowers in deep eutectic solvent at low temperature and their application in organic electro-oxidation - Aoqi Li (Nature Portfolio, 2018)
Abstract Deep eutectic solvents (DESs), called a new generation of green solvents, have broad applied in synthesis of nanomaterials due to their remarkable physicochemical properties. In this work, we used a unique strategy (adding moderate water (10%) to DES) to effectively prepare nanomaterials. Flower-like AuPt alloy nanoparticles were successfully synthesized using one-step electrochemical reduction method at a low potential of −0.30 V (vs. Pt) and a low temperature of 30 °C. In this process, the DES acted as solvent and shape-directing agent. More importantly, we used the electrode modified with the as-prepared nanomaterials as the anode to the electrochemical oxidation synthesis. The glassy carbon electrode modified with the AuPt nanoflowers was directly employed to the electro-oxidation of xanthene (XT) to xanthone (XO) under a constant low potential of 0.80 V (vs. Ag/AgCl) and room temperature, with a high yield of XO. Moreover, the synthesis process was milder and more environment-friendly than conventional organic syntheses. This new strategy would have a promising application in electroorganic synthesis fields.